From Low-Dose Fixed Combinations for Arterial Hypertension Treatment to Multi-Target Therapy of Cardiovascular Diseases - P. A. Lebedev; A. A. Garanin (Рациональная фармакотерапия в кардиологии)
The article presents the evolutionary development of combination therapy from the creation of a multicomponent tablet for the treatment of arterial hypertension (AH) to modern multi-target fixed combinations as the most effective approach to the fight against cardiovascular diseases (CVD). The priority of domestic scientists, in particular academician A.L. Myasnikov, in the development and creation of a combined drug for AH treatment is shown. The development of pharmacology and pharmaceutical technologies has allowed to expand the range of possible drug combinations for AH therapy, and the discovery of new pathophysiological mechanisms involved in the cardiovascular continuum has led to the understanding of the close links between AH and atherosclerosis. This fact prompted the scientific community to search for and implement in practice drug combinations that would allow multi-target therapy, that is, to influence several pathological processes and achieve a number of therapeutic goals. The presented review testifies to the transformation of the concept of fixed combinations for patients with AH into the concept of a multi-target drug. Multi-targeting is achieved not only by the pleotropic of components known as hypotensive agents, but also by combination with statins. Taking into account the wide AH prevalence in the population, its high medical and social significance, the critical importance as a risk factor for CVD, the authors consider a justified clinical and epidemiological approach to primary prevention of CVD with the widespread use of multi-targeted therapy in all high-risk patients with AH. It is expedient to develop new domestic medicines that implement the concept of a multi-targeted drug, to include them in the list of vital medicines, to increase the availability of these drugs to the population on the basis of preferential programs.